Comparison of Dual Energy X-Ray Absorptiometry and Quantitative Ultrasonography Measurements in Osteoporotic Patients - Original Investigation - Şule Tütün; Derya Saylık; Levent Özgönenel; Esra Çetin; Gülis Kavadar; Şeyma Tolga; Şafak Günaydın (Galenos Yayinevi, 2008)
Aim: Osteoporosis (OP) is a skelatal disease of bone fragility resulting from micro-architectural deteriotarion and decreased bone mass. There are many studies in literature that show high sensibility and specifity of quantitative ultrasonography (QUS). Recently many comparatives studies of QUS and dual energy X-ray absorbtiometry (DEXA) have been made. In this study we aimed to investigate correlation of QUS and DEXA measurments in 53 women with postmenopausal osteoporosis were enrolled in this study. Material and Method: Fifty three postmenopausal women with osteoporosis were studied: Ultrasound parameters were measured by the DTU-one imaging ultrasonometer in the calcaneus. BMD was assessed by dual-energy X-ray absorptiometry (DEXA) at the lumbar spine, femoral neck, and trochanter. QUS measurements of the postmenopausal women was compared with DEXA measurements. Results: There was a significant correlation between QUS T scores and DEXA L2-L4 T scores (r =0.463 p=0.000 p<0.005), there was a significant correlation between QUS Z scores and DEXA L2-L4 Z scores (r =0.589 p=0.000 p<0.005 ), there was a significant correlation between QUS T scores and DEXA femur neck T scores (r =0.463 p=0.000 p<0.005 ), there was a significant correlation between QUS Z scores and DEXA femur Z scores (r =0.418 p=0.000 p<0.005). Conclusion: Consequently QUS results were correlated with DEXA results in postmenopausal osteoporotic patients. (From the World of Osteoporosis 2008;14:26-8)